2015
DOI: 10.15298/rusentj.24.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic signals of the bush-crickets of tribe Barbitistini (Orthoptera: Tettigoniidae: Phaneropterinae) from Eastern Europe and Caucasus. II. Leptophyes Fieber, 1853, Euconocercus Bey-Bienko, 1950, Barbitistes Charpentier, 1825, Polysarcus Fieber, 1853

Abstract: 2013], but songs of species from the South of the East Europe, Caucasus and Transcaucasia are less known. Sound signals of only a few phaneropterine bush-crickets are described [op. cit.; Zhantiev, Korsunovskaya, 1986, 1990, Korsunovskaya, 2015]. We suppose that it is interesting and useful to compare the comprehensive studied songs of specimens from West European populations (e.g. Leptophyes albovittata (Kollar, 1833) and Barbitistes constrictus Brunner von Wattenwyl, 1878) with corresponding data concerning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Here, we see similar tradeoffs in acoustic signals, but over 24 hour timescales and across a subfamily rather than within a genus. Interestingly, closely related Phaneropterinae that occupy other habitats produce substantially more sound (Heller and von Helversen 1993;Zhantiev and Korsunovskaya 2005), indicating that the tradeoffs seen in this study are likely a property of the habitat, not the entire taxonomic group, and that species have conformed to this relationship through multiple instances of colonization and evolution. The pervasiveness of tradeoff relationships across species highlights the potential existence of broad structuring principles that shape the spatial and temporal dynamics of communication across taxa.…”
Section: Figmentioning
confidence: 72%
“…Here, we see similar tradeoffs in acoustic signals, but over 24 hour timescales and across a subfamily rather than within a genus. Interestingly, closely related Phaneropterinae that occupy other habitats produce substantially more sound (Heller and von Helversen 1993;Zhantiev and Korsunovskaya 2005), indicating that the tradeoffs seen in this study are likely a property of the habitat, not the entire taxonomic group, and that species have conformed to this relationship through multiple instances of colonization and evolution. The pervasiveness of tradeoff relationships across species highlights the potential existence of broad structuring principles that shape the spatial and temporal dynamics of communication across taxa.…”
Section: Figmentioning
confidence: 72%
“…A this paperB Dagmar von Helversen, unpublishedC Heller (1988)D Heller et al (2015)E Iorgu (2012a)F Robinson et al (1986)G Zhantiev and Korsunovskaya (1986)H Zhantiev and Korsunovskaya (2015)…”
Section: Resultsmentioning
confidence: 93%
“…The acoustic response behaviour of the female was first studied by Zhantiev and Korsunovskaya (1986, 1990, 2015). They showed that the female latency time is constant with reference to the beginning of the song.…”
Section: Resultsmentioning
confidence: 99%
“…Specimen identification followed morphological descriptions (see Bey-Bienko, 1954;Chobanov et al, 2015;Kaya et al, 2012;Ramme, 1933;Ünal, 2005, 2010Zhantiev & Korsunovskaya, 2015).…”
Section: Taxon Sampling and Identificationmentioning
confidence: 99%
“…Such character‐based species definitions imply a direct link to a mechanism of reproductive isolation, and such characters are, therefore, a prime candidate for understanding the bush cricket's diversification (Heller et al, 2015; Heller & Hemp, 2020). However, sometimes there are individuals of intermediate morphologies between species, which has fuelled taxonomic discrepancies (Borissov et al, 2023; Chobanov et al, 2015; Kaya et al, 2012; Ramme, 1933; Tarbinsky, 1932; Ünal, 2012; Zhantiev & Korsunovskaya, 2015). Moreover, variation in the cerci (namely, in length, curvature, thickness, apical structure and the number/orientation of distal teeth) and variation in temporal parameters of the three types of male calling song (see Chobanov et al, 2015; Kaya et al, 2012) may represent a breakdown of reproductive barriers, or the ephemerality of incipient species divergences (Rosenblum et al, 2012).…”
Section: Introductionmentioning
confidence: 99%